Placental pathology and its correlation with immediate feto neonatal outcome - A., Ashoka; Sarthi, Manjunatha; C., Basavraj A.; K., Mahesh T. (International Journal of Contemporary Pediatrics, 2019)
Background: Placenta plays a major role in growth and development of the fetus as it helps in both exchange of nutrients and removal of waste. Even though it yields a valuable information of prognostic significance for the newborn, majority of the time it will be discarded after the gross examination. Hence the present study was conducted to determine the placental pathology and its correlation with fetal outcome. Methods: The present study was carried out in Davangere for a period of 2 years. The placenta of 100 parturients, more than 28 weeks of gestation were included for the present study. The data was collected after detailed review of the obstetric case records. Placentas were examined soon after delivery. After the gross examination was complete, the placentas were put in a labelled plastic container. The placentas were re-examined macroscopically again by the pathologist. Cut-section examination was done. Then, at least 4 appropriate blocks were taken for each placenta. They were stained with hematoxylin-eosin stain and examined under the microscope. The histopathological examination was conducted as per proforma. Results: One hundred placentae belonging to one hundred babies were studied among which 80% of the maternal cases had anaemia, 68% were term infant, 37% had IUGR. Eccentric insertion of the cord was observed to be the commonest (51). Marginally inserted membranes were seen most frequently (97). Conclusions: In the present study we conclude that placental reserve is large and small alteration do not affect the pregnancy outcome. The placental changes are not specific to a particular condition affecting the pregnancy.